Taenia crassiceps injection into the subarachnoid space of rats simulates radiological and morphological features of racemose neurocysticercosis - Hamamoto Filho, Pedro Tadao [UNESP] (2017)
Purpose: Neurocysticercosis is a major public health concern. Although its eradication appears feasible, the disease remains endemic in developing countries and has emerged again in Europe and in the USA. Basic studies on neurocysticercosis are needed to better understand the pathophysiologic mechanisms and, consequently, to improve treatment perspectives. Much has been published on experimental parenchymal neurocysticercosis, but there are no experimental models of racemose neurocysticercosis. Methods: Cysts of Taenia crassiceps were injected into the subarachnoid space of 11 rats. After 4 months, magnetic resonance imaging (MRI) was performed to verify the occurrence of ventricular dilatation and the distribution of cysts in the cerebrospinal fluid compartments. The histologic assessment was done focusing on changes in the ependyma, choroid plexus, and brain parenchyma. Results: MRI and histologic assessment confirmed the findings similar to those seen in human racemose neurocysticercosis including enlargement of the basal cisterns, hydrocephalus, and inflammatory infiltration through the ependyma and choroid plexus into cerebrospinal fluid spaces. Conclusions: We developed a simple model of racemose neurocysticercosis by injecting cysts of T. crassiceps into the subarachnoid space of rats. This model can help understand the pathophysiologic mechanisms of the disease.